Tart Cherry Supplement Enhances Skeletal Muscle Glutathione Peroxidase Expression and Functional Recovery after Muscle Damage. Issue 4 (9th April 2022) - Wangdi, Jimmy T.; O'Leary, Mary F.; Kelly, Vincent G.; Jackman, Sarah R.; Tang, Jonathan C. Y.; Dutton, John; Bowtell, Joanna L.
ABSTRACT: Introduction: Montmorency cherry concentrate (MCC) supplementation enhances functional recovery from exercise, potentially due to antioxidant and anti-inflammatory effects. However, to date, supporting empirical evidence for these mechanistic hypotheses is reliant on indirect blood biomarkers. This study is the first to investigate functional recovery from exercise alongside molecular changes within the exercised muscle after MCC supplementation. Methods: Ten participants completed two maximal unilateral eccentric knee extension trials after MCC or placebo (PLA) supplementation for 7 d before and 48 h after exercise. Knee extension maximum voluntary contractions, maximal isokinetic contractions, single leg jumps, and soreness measures were assessed before, immediately, 24 h, and 48 h after exercise. Venous blood and vastus lateralis muscle samples were collected at each time point. Plasma concentrations of interleukin-6, tumor necrosis factor alpha, C-reactive protein, creatine kinase, and phenolic acids were quantified. Intramuscular mRNA expressions of superoxide dismutase 1 (SOD1), SOD3, glutathione peroxidase 1 (GPX1), GPX3, GPX4, GPX7, catalase, and nuclear factor erythroid 2–related factor 2 and relative intramuscular protein expressions of SOD1, catalase, and GPX3 were quantified. Results: MCC supplementation enhanced the recovery of normalized maximum voluntary contraction 1-s average compared with PLA (postexercise PLA, 59.5% ± 18.0%, vs MCC, 76.5% ± 13.9%; 24 h PLA, 69.8% ± 15.9%, vs MCC, 80.5% ± 15.3%; supplementation effect P = 0.024). MCC supplementation increased plasma hydroxybenzoic, hippuric, and vanillic acid concentrations (supplementation effect P = 0.028, P = 0.002, P = 0.003); SOD3, GPX3, GPX4, GPX7 (supplement effect P < 0.05), and GPX1 (interaction effect P = 0.017) gene expression; and GPX3 protein expression (supplementation effect P = 0.004) versus PLA. There were no significant differences between conditions for other outcome measures. Conclusions: MCC supplementation conserved isometric muscle strength and upregulated antioxidant gene and protein expression in parallel with increased phenolic acid concentrations.